Humanistic Psychology In Student Behavior That Often Truant - Prabowo, Alfian Dewan Adhayuda (International Journal for Educational and Vocational Studies, 2020)
In this journal review the views of humanistic psychology towards students who often play truant . Which it will discuss : the sense psikl Ogi humanistic, historical brief emergence of humanistic education and pen ge rtian humanistic education , as well as reviewing the behavior of ditching. The selection of this humanistic approach is not without reason, because the cases that occur with students who play truant are related to the element of humanity. Where the meaning of education in humanistic is the process of humanizing humans, so what is the background students play truant and unable to actualize themselves. So just like the counseling process we deal with individuals tailored between cases and what approaches are right to solve them. The purpose of this study is to find out why students often play truant , then study humanistic psychology . This type of research used in this research is descriptive qualitative. Data collection techniques used were structured interviews. Data analysis technique used to process data is qualitative data analysis. The research subjects were 1 student and 1 counseling teacher as a source triangulation. The result is students often play truant in the play station game, because they feel less attention from parents (fathers). In conclusion Students who are less attentive than parents have a behavior of their own accord.